Responsabilidade : sobre a consciência moral e a alteridade no pensamento de Viktor Frankl e Emmanuel Levinas - Mota, Gustavo Rubin da (2013)
Responsibility is the term connection between the thought of Emmanuel Levinas and Viktor Frankl, by which is consistent moral consciousness as a possible encounter with another human. Freedom and responsibility before any deliberate or intentional subject, in which the respondent by human indigence of another Master who reports to break the monism of a strong bio psyche and sociology, whose predominant aspect is the person in charge of any condition. Consciousness previous intelligibility while Bad conscience that does not close in a circularity of Even, putting into crisis selfhood and meaning to be found and updated in meetings and confrontation with the social meanings . Encounters through the traces inscribed in face epiphenomenon of the other's presence and Absent, the "He" that is the otherness that recognizes the other in its absolute say. Pronounceable say the flow of time in sensitivity brought to disinterestedness and input Others meeting as anarchical and dissymmetry, causing the other the trauma of what would be the obvious. Meaning of life post as liability prior to any free initiative of the subject, which collects on the Other traces of the third, the "He" look like infinitive - face that speaks to me, I want the clutter in your selfhood, and exposes the human to justice before the others, absolutely another. Confrontation with the responsibility of nakedness and misery of Others, which calls for the unity of the one- respondent, taking him hostage in unconditional replacement source of appeal arising from (Illeité) he-ity and calls for replacement, give support to the less is more, the infinite in ethical language.